Pelatihan Literasi Digital bagi Orang Tua: Langkah Menuju Keluarga Cerdas Digital - Desi Novianti; Yogi Bachtiar; Dewi Anjani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
At RT 06/014 Kel. Palmerah, West Jakarta, there is an urgent need to increase digital literacy among parents, who vary in age and level of technological knowledge. Reliance on digital technology poses challenges in supervising children and online safety. This challenge can be overcome by conducting digital literacy training designed to close knowledge gaps, improve online security, and provide skills to use technology responsibly. This training is carried out through lectures, simulations, and practice. Survey results showed high satisfaction (4.2/5) with the training content, but there was demand for more hands-on activities, especially regarding social media and data security. This training aims to equip parents with the skills necessary to support their children's education in a dynamic digital environment.